2019
DOI: 10.5812/compreped.86902
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Mortality Rates for Leading Causes of Death Among Under-Five Children in Iran, 2000 - 2015

Abstract: Background: This secondary study is the first to assess the trend of mortality rate and its variations among Iranian children. Methods: The mortality data of under-five children were extracted from the WHO reports. All-cause and cause-specific mortality rates were calculated per 1000 live births and by age groups for each year from 2000 to 2015. The average annual rate of reduction (AARR) was used to determine the changes in mortality rates. Results: Of 21011 under-five children who died in 2015, 52.3% were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There were three studies with information on pertussis-related deaths, including one from Israel [44] and two in Iran [45,46].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three studies with information on pertussis-related deaths, including one from Israel [44] and two in Iran [45,46].…”
Section: Search Resultsmentioning
confidence: 99%
“…Based on an analysis of published literature, the GBD estimates of pertussis-related mortality in Iran in 2010 were 0.3025/100,000 in children aged \ 5 years and 0.0009/100,000 in people aged 15-49 years [46]. However, among notified pertussis deaths in Iran in 2015, the mortality rate among young children was higher than previous GBD estimates at 0.176/ 1000 live births among children aged \ 5 years [45]. The pertussis CFR was reported by one study, which showed that in Israel in 1999-2016, there were 19 deaths in infants, at a CFR of 0.7% [44].…”
Section: Discussionmentioning
confidence: 99%